Demand for cigarettes in Uruguay: a national analysis with monthly data - Zuleika Ferre; Mariana Gerstenblüth; Patricia Triunfo (Discover Public Health)
Abstract This study examines the demand for legally sold cigarettes in Uruguay from January 1997 to June 2022. Time series analysis reveals that cigarette demand is consistently inelastic, with a price elasticity of – 0.77 and an income elasticity of 0.34. Tobacco control policies—such as 100% smoke-free spaces (since March 2006), single presentation (since February 2009), a comprehensive advertising ban (since November 2014), and neutral packaging (since January 2020)—have significantly reduced cigarette demand. While isolating the impact of each policy is challenging, their collective effectiveness in curbing cigarette consumption is evident. In line with the WHO's Framework Convention on Tobacco Control, we simulated progressive tax increases from 2024 to 2028. The analysis suggests that a 60% real-term increase in the specific cigarette tax (IMESI) would reduce the smoking population by 8.82%, resulting in 49,000 fewer smokers during the period, and an 18.65% decrease in legal cigarette consumption. Despite an 4.46% decline in real tax revenue between 2022 and 2023, our projections indicate that these tax adjustments could increase tax revenue by 24.35%.